Room temperature polariton spin switches based on Van der Waals superlattices - Zhao, Jiaxin (2024)
Transition-metal dichalcogenide monolayers possess large exciton binding energy and a robust valley degree of freedom, making them a viable platform for the development of spintronic devices capable of operating at room temperature. The development of such monolayer TMD-based spintronic devices requires strong spin-dependent interactions and effective spin transport. This can be achieved by employing exciton-polaritons. These hybrid light-matter states arising from the strong coupling of excitons and photons allow high-speed in-plane propagation and strong nonlinear interactions. Here, we demonstrate the operation of all-optical polariton spin switches by incorporating a WS2 superlattice into a planar microcavity. We demonstrate spin-anisotropic polariton nonlinear interactions in a WS2 superlattice at room temperature. As a proof-of-concept, we utilize these spin-dependent interactions to implement different spin switch geometries at ambient conditions, which show intrinsic sub-picosecond switching time and small footprint. Our findings offer new perspectives on manipulations of the polarization state in polaritonic systems and highlight the potential of atomically thin semiconductors for the development of next generation information processing devices.